Analysis And Comparative Study Of Topical Conservative Medication Versus Operative Management In Patients Of Anal Fissure (Indian Journal of Applied-Basic Medical Sciences, 2022)
Introduction:Anal fissures or anal ulcers are considered one of the commonest causes of severe anal pain. Surgical techniques like manual anal(lords) dilatation or lateral internal sphincterotomy, effectively heal most fissures within a few weeks, but may result in permanently impaired anal continence. This has led to the research for alternative non-surgical treatment AIMS AND OBJECTIVES:The present study comprises the comparative study of 2% Diltiazem gel,0.2% Glyceryl Nitrate,2% lignocaine jelly application and need of surgical intervention in the treatment of chronic fissure in ano.MATERIALS AND METHODS:This is a prospective study of fissure in ano during the period from September 2020 to September 2021 in Sheth Lallubhai Gordhandas Municipal General Hospital, Ahmedabad. Clinical Data of admitted patient were collected by their detail history after stabilizing the patient, clinical examination with appropriate investigations. OBSERVATION AND DISCUSSION: Anal fissure is a very common problem across the world. It causes considerable morbidity and adversely affects the quality of life. Therefore appropriate treatment is mandatory.In this study the commonest age group affected was 31-40 years age group (40%) and least affected were 51-60 years age group The incidence of fissure in males was slightly greater than females with Male Female ratio being 2.2: 1 in our study. CONCLUSION: Propper clinical examination and appropriate investigations helps in management of patient either operative or non-operative which leads successful treatment in these patients.
Keywords: Fissure in ano; site of fissure; pain relief; Nitroglycerin; Diltiazem